Persistence of Human Papillomavirus DNA in Cervical Lesions After Treatment With Diathermic Large Loop Excision - A. L. Distéfano; M. A. Picconi; L. V. Alonio; D. Dalbert; J. Mural; O. Bartt; G. Bazán; G. Cervantes; M. Lizano; A. G. Carrancá; A. Teyssié (Hindawi Limited, 1998)
Objective: The aim of this study was to identify human papillomavirus (HPV) in cervical intraepithelial neoplasia (CIN) lesions and to evaluate the persistence of viral DNA after diathermic large loop excision (DLLE) treatment.